Discoveries and Other Information in Physics and Astronomy of the Last Decade, which Have a Potential to Influence our View on the Universe - Emil Betak; Franc Cvelbar (Communications - Scientific letters of the University of Zilina, 2017)
In the last decade, natural sciences (sometimes called exact sciences) have nearly every week brought some discoveries or important news, which have consequences on our understanding of the world and the whole Universe, its past and future, and which may stimulate possible new philosophical look at the world and human beings in it. We have selected several such cases and will try to present them to colleagues working outside the natural sciences to serve as motives for their work: i) Water, the basic liquid for our life, seems to be much more abundant (though not in clear form without ingredients) on and inside the Earth and in the Universe than was assumed still a decade ago. What does it mean and which are the consequences for us? ii) Is our Earth the only place of intelligent life in the Universe or not? What do both these possibilities mean for us, for philosophy, ethics and theology? iii) Nature is full of various surprises, which may come as a disaster in a global scale. Are we prepared to cope with them?